The COVID-19 pandemic: impact and strategies for sports and exercise medicine researchers during large-scale social restrictions - Borges, L.; Moraes, M. M.; Arantes, R. M.; Hatanaka, E. (Journal of Medical Systems, 2021)
There are currently two global pandemics: COVID-19 and physical inactivity [1]. Since the World Health Organization states nearly 2 million deaths per year to sedentary lifestyle [2], exercise medicine becomes even more relevant since sports medicine research (SMR) generates the theoretical framework for prescription and evidence-based approaches, which allows the population - from athletes to the elderly - to exercise in an optimized and safe manner. We herein outline the foreseeable impact of COVID-19 on SMR and point to tips to minimize the pandemic`s influence on exercise intervention studies.